Invasive species do not exploit early growing seasons in burned tallgrass prairies. Issue 7 (13th June 2022) - Ratcliffe, Hugh; Ahlering, Marissa; Carlson, Daren; Vacek, Sara; Allstadt, Andrew; Dee, Laura E.
Abstract: Invasive species management is key to conserving critically threatened native prairie ecosystems. While prescribed burning is widely demonstrated to increase native diversity and suppress invasive species, elucidating the conditions under which burning is most effective remains an ongoing focus of applied prairie ecology research. Understanding how conservation management interacts with climate is increasingly pressing, because climate change is altering weather conditions and seasonal timing around the world. Increasingly early growing seasons due to climate change are shifting the timing and availability of resources and niche space, which may disproportionately advantage invasive species and influence the outcome of burning. We estimated the effects of burning, start time of the growing season, and their interaction on invasive species relative cover and frequency, two metrics for species abundance and dominance. We used 25 observed prairie sites and 853 observations of 267 transects spread throughout Minnesota, USA from 2010 to 2019 to conduct our analysis. Here, we show that burning reduced the abundance of invasive cool‐season grasses, leading to reduced abundance of invasive species as a whole. This reduction persisted over time for invasive cover but quickly waned for their frequency of occurrence. Additionally, and contrary to expectations that early growing season starts benefit invasive species, we found evidence that later growing season starts increased the abundance of some invasive species. However, the effects of burning on plant communities were largely unaltered by the timing of the growing season, although earlier growing season starts weakened the effectiveness of burning on Kentucky bluegrass ( Poa pratensis ) and smooth brome ( Bromus inermis ), two of the most dominant invasive species in the region. Our results suggest that prescribed burning will likely continue to be a useful conservation tool in the context of earlier growing season starts, and that changes to growing season timing will not be a primary mechanism driving increased invasion due to climate change in these ecosystems. We propose that future research seek to better understand abiotic controls on invasive species phenology in managed systems and how burning intensity and timing interact with spring conditions.